A Review on the Antidiabetic Properties of Moringa oleifera Extracts: Focusing on Oxidative Stress and Inflammation as Main Therapeutic Targets - Mthiyane, Fikile T.; Dludla, Phiwayinkosi V.; Ziqubu, Khanyisani; Mthembu, Sinenhlanhla X. H.; Muvhulawa, Ndivhuwo; Hlengwa, Nokulunga; Nkambule, Bongani B.; Mazibuko-Mbeje, Sithandiwe E. (Frontiers in Pharmacology, 2022)
Moringa oleifera is one of the popular plants that have shown significant health benefits. Certainly, preclinical evidence (predominantly from animal models) summarized in the current review supports the beneficial effects of Moringa oleifera leaf extracts in combating the prominent characteristic features of diabetes mellitus. This includes effective control of blood glucose or insulin levels, enhancement of insulin tissue sensitivity, improvement of blood lipid profiles, and protecting against organ damage under sustained conditions of hyperglycemia. Interestingly, as major complications implicated in the progression of diabetes, including organ damage, Moringa oleifera leaf and seed extracts could efficiently block the detrimental effects of oxidative stress and inflammation in these preclinical models. Notably, these extracts (especially leaf extracts) showed enhanced effects in strengthening intracellular antioxidant defences like catalase, superoxide dismutase, and glutathione to lower lipid peroxidation products and reduce prominent pro-inflammatory markers such as tumor necrosis factor-α, interleukin (1L)-ꞵ, IL-6, monocyte chemoattractant protein-1 and nitric oxide synthase. From animal models of diabetes, the common and effective dose of leaf extracts of Moringa oleifera was 100-300 mg/kg, within the treatment duration of 2 to 8 weeks. Whereas supplementation with approximately 20 g leaf powder of Moringa oleifera for at least 2 weeks could improve postprandial blood glucose is subjects with prediabetes or diabetes. Although limited clinical studies have been conducted on the antidiabetic properties of Moringa oleifera, current findings provide an important platform for future research directed at developing this plant as a functional food to manage diabetic complications.